Poly-victimization & Resilience Portfolios: Advancing the Science of Resilience Following Children's Exposure to Violence, Alabama, Georgia, Mississippi, Tennessee, 2016-2018 - Hamby, Sherry L. ([Verlag nicht ermittelbar], 2019)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. The objective of this project was to use a mixed methods approach to expand the understanding of constructs important to resilience after children's exposure to violence (CEV), expand the range of outcomes examined, develop and refine measures appropriate for youth, and identify protective factors that could be targets for prevention and intervention. Eight focus groups and 24 cognitive interviews were conducted with parents and youth to explore resilience constructs. These were followed by a survey completed by 440 youth ages 10 to 21, recruited from youth-serving organizations. Key variables in this collection include demographics such as age, gender, and education; experience of violence; and physical and psychological well-being. The data collection includes: Survey data file, NCAC.CEVres.survey-data_Updated.sav, n=440, 208 variables Focus group data file, NCAC.CEVres.Focus-group-transcripts.pdf, n=70 Cognitive interview data file, NCAC.CEVres.Cognitive-interview-transcripts_updated.pdf, n=24 The focus group and interview data files are not available at this time, even under restricted use.